RELEVANSI KARYA SASTRA DI SURAT KABAR DENGAN PEMBELAJARAN SASTRA DI SEKOLAH MENENGAH PERTAMA - Main Sufanti; Nuraini Fatimah (Kajian Linguistik dan Sastra, 2013)
The study aims at descibing the relevance of literary works published by newspapers with the basic competence of Bahasa Indonesia subject for junior high school (SMP), and the levels of physchological development of junior high school students. This study involves research and development approach in which the first year project applies desriptive qualitative method. The data take the forms of words, phrases, sentences, and discourse of literary works gathered from two newspapers, Solopos and Kompas issued in January and February 2011. The data is analyzed by critical and comparative methods. The results show that (1) not all literary works found in Solopos and Kompas agree with the basic competence of Bahasa Indonesia subject for junior high school, excepts children’s story, poetry, short story, and picture story which comprise 64% of total data. Other works such as novel and poems comprising 36% of the basic competence were not found in the newspapers. (2) Not all literary works published by the two newspapers are appropriate to the psychological development of the students of junior high school. Only 49% of literary works were relevant to both basic competence and psychological development of the students. Nevertheless each newspaper provides different quantity of the relevance; as for Solopos, out of 54 literary works, 37 (69%) were relevant, and for Kompas, out of 131 literary works, only 40 (31%) were applicable.